Where are they all from? – sources and sustainability in the ornamental freshwater fish trade. Issue 6 (8th April 2019) - Evers, Hans‐Georg; Pinnegar, John K.; Taylor, Martin I.
Abstract : The global trade in ornamental fish involves c . 125 countries worldwide and is worth c . US $15–30 billion each year. This total is dominated (90%) by freshwater fishes, most of which are sourced from breeding facilities located in developing countries, typically in Asia or South America, but also in Israel, USA and Europe. Some fish are still obtained from natural (wild) sources, but the exact percentage of wild‐caught fish is difficult to quantify given a lack of reliable data. Although c . 1000 species of freshwater fishes are widely available (from a total of > 5300 on sale), the most dominant freshwater fishes in the market comprise only 30 species from the orders Cyprinodontiformes, Perciformes, Characiformes and Siluriformes. In this perspectives review paper, illustrative example case studies of wild‐fish collecting (Barcelos and Rio Xingu, Brazil) and breeding projects (Java, Indonesia) are described. In addition, wild‐collecting expeditions to West Papua, Indonesia are discussed, focused on discovering novel species of rainbowfish (Melanotaeniidae) for breeding in captivity. Sustainability of the aquarium industry is considered in its broadest sense. The aquarium industry has been portrayed as both a major threat to natural ecosystems, but also as being part of the solution in terms of helping to maintain species when they have gone extinct in the wild or offering an income to impoverished citizens who might otherwise engage in much more destructive practices.